Aiming for Excellence: Reflections on the Advanced Institute of Management Research and its Elite. (8th November 2015) - Macdonald, Stuart; Steen, John; Shazi, Rahmat
Abstract : In 2002, the UK government launched the Advanced Institute of Management Research, a major initiative intended to raise the quality of research in business schools. Rather than offering research grants in open competition, AIM deliberately funded a select few leading lights in management. Insufficient allowance was made for the Research Assessment Exercise, which measured research excellence in terms of papers published in top journals. The AIM's elite exploited its existing publishing advantage, and AIM provided further resources to aid their efforts. The AIM recruited willing acolytes to work with its elite in fashioning the sort of papers required by the top journals of management – positive papers, consensual and endlessly citable. Analysis of the publishing patterns of AIM senior fellows reveals research cliques and publication silos rather than a network organization. Much as the elite saw its AIM funding as recognition of its own excellence, so AIM itself came to be seen as acknowledgement of the excellence of management research as a whole. That AIM existed to raise management research from intellectual poverty was forgotten. The AIM was wound up in 2012, having spent £30 million, most of it on the subject's elite. The problems that beset management research remain.